2010
DOI: 10.1590/s0103-50532010001000024
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, structural, microhardness and corrosion characterisations of electrodeposited Ni-Mo and Cr coatings

Abstract: A resistência à corrosão de eletrodepósitos de Cr e Ni-Mo e a influencia do tratamento térmico na estrutura cristalográfica, na morfologia e nas propriedades de microdureza foram investigados. As caracterizações foram feitas usando as técnicas de microscopia eletrônica de varredura (SEM), difração de raios X (XRD) e energia dispersiva de raios X (EDX). Os ensaios de corrosão foram feitos à temperatura ambiente, em solução de NaCl 10 -1 mol dm -3 e usando a técnica de polarização linear potenciodinâmica. O teor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 12 publications
2
25
0
Order By: Relevance
“…The observed spherical nodules are explained as a consequence of the growth of secondary nuclei on top of the first layer that was formed on the substrate surface. It has previously been reported in the literature 10,12 that cracked Ni-Mo electrodeposits were obtained when the Mo content in the layer was higher than 17 at.%. Thus, Figure 3A shows that 1 at.% of P is not enough to avoid the formation of a cracked Ni−Mo−P layer which can compromise the corrosion resistance and hardness properties of this coating.…”
Section: Influence Of the Plating Parametersmentioning
confidence: 93%
See 4 more Smart Citations
“…The observed spherical nodules are explained as a consequence of the growth of secondary nuclei on top of the first layer that was formed on the substrate surface. It has previously been reported in the literature 10,12 that cracked Ni-Mo electrodeposits were obtained when the Mo content in the layer was higher than 17 at.%. Thus, Figure 3A shows that 1 at.% of P is not enough to avoid the formation of a cracked Ni−Mo−P layer which can compromise the corrosion resistance and hardness properties of this coating.…”
Section: Influence Of the Plating Parametersmentioning
confidence: 93%
“…9 Recently, we showed that electrodeposited Ni−Mo coatings presented inferior corrosion-resistance and hardness properties in comparison to electrodeposited Cr coatings. 10 However, after heat treatment at temperature higher than 100 °C, these coatings presented superior hardness properties in comparison to the heat-treated Cr coatings. These results indicated that Ni−Mo coatings could be a potential substitutes for chromium coatings in industrial applications in which operational temperatures higher than 100 °C and good hardness properties are required.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations